ANALYSIS OF FACTORS AFFECTING THE VOLUME OF APPLE IMPORTS IN INDONESIA - Elpawati Elpawati; Puspi Eko Wiranthi; Gita Tri Nurraini (AGRIBUSINESS JOURNAL, 2020)
Apples are one of the subtropical fruits with the highest volume compared to other imported fruits from 2008 to 2017. The high volume of imported apples is caused by the fact that domestic apple production is not sufficient for consumption. This study aims to see what factors can influence the importance of apples in Indonesia and what factors have the greatest influence. The variables used in this study are local apple production, consumption of Indonesian apples, real GDP per capita of developing countries, real GDP per capita of Indonesia, economic distance, real exchange rates, and Indonesian population. This research uses panel data regression analysis method with PPML Gravity Model estimation approach. This study uses cross section data, namely 9 countries that have apples to Indonesia and time series data, namely Indonesian apple import data for 10 years from 2008 to 2017. The commodity studied was fresh apples with HS code 080810. The variables that have a significant effect on import volume apples in Indonesia, namely real GDP per capita of developing countries, real GDP per capita of Indonesia, economic distance, and population of Indonesia.